Gambaran Tingkat Pengetahuan Tentang Periksa Payudara Sendiri (SADARI) pada Mahasiswi Universitas ‘Aisyiyah Surakarta - Lisa Aryanti; Sitti Rahma Soleman (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Breast cancer has a fairly high mortality and is a type of malignancy that often attacks women. Breast cancer is a type of malignant disease that is very feared by women because breast cancer ranks first after cervical cancer. The magnitude of the problem of breast cancer incidence requires health intervention in the form of national management. One of the efforts to control breast cancer is to use breast self-examination (BSE), which women can do themselves as an effective and safe early detection tool for breast cancer. This study aims to describe the level of knowledge about Breast Self-Examination (BSE) among female students at 'Aisyiyah University, Surakarta. This study used a quantitative descriptive method, with a study population of 1,160 female students with a total sample of 92 respondents, and used a stratified random sampling technique. By using a questionnaire that is distributed directly by researchers who are distributed randomly. The results of the research on 'Aisyiyah Surakarta University students showed that 47 respondents (51.1%) had a good level of knowledge, the sufficient category was 28 respondents (30.4%). As for the lacking category, there were 17 respondents (18.5%). The conclusion of the respondents was that the majority of female students got good knowledge.